Implementasi Alat Permainan Edukatif (APE) Keterampilan Meronce untuk Menumbuhkan Perkembangan Sensorik dan Motorik Anak Usia Dini - Sofie Anggraeni; Mu’ammar Mu’ammar; Asrul Faruq; Nida Adilah (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Meronce is the process of arranging or assembling objects by inserting perforated objects into a string or thread to create beautiful works. This meronce skill not only develops the sensory and motor aspects of children, but also enhances focus on the senses, such as concentration, training social-emotional skills, cognitive skills, as well as introducing colors and shapes to children aged 5-6 years. By taking beads and arranging them according to desired patterns or shapes, children can practice hand movements, eye coordination, and motor skills. The use of meronce skills in learning is very effective in developing various aspects of early childhood development, both in kindergarten and early childhood education. Therefore, this article discusses the use of Educational Play Equipment (APE) Meronce Skills to enhance sensory and motor development in early childhood. This study uses a qualitative approach with field research, which aims to determine the background, social groups, individuals, and community institutions. The results show that meronce skill learning in classroom B1 of TK Muslimat Nurul Ulum 2 Pegiringan is conducted with enthusiasm, creativity, and high spirits. Children are able to follow their teacher's instructions well.